Personal norms and the adoption of pro-environmental binning behaviour in national parks: an integrated structural model approach. Issue 1 (2nd January 2020) - Esfandiar, Kourosh; Dowling, Ross; Pearce, Joanna; Goh, Edmund
Abstract: A pro-environmental behaviour to solve the problem of litter management in the national parks is binning. This study is the first to explore the factors affecting an individual's binning behaviour in the context of a national park. Drawing on theories with self-interest (i.e. theory of planned behaviour) and other-interest/pro-social (i.e. norm-activation model) motives, an integrated structural model of binning behaviour (IMB) was developed. Our study analysed data from visitors (n = 240) to Sorkh-e-hesar National Park in Iran. Based on our proposed integrated theory of planned behaviour and norm activation model, the partial least squares structural equation modelling (PLS-SEM) provided satisfactory empirical anticipatory efficacy for binning behaviours. The PLS-SEM results revealed the association between awareness of consequences and personal norms was the strongest, and personal norm was the most influential determinant of pro-environmental binning behaviour. The results also showed that attitude had no significant effect on binning behaviour but was influenced by awareness of consequences. Moreover, a salient role of personal norms in predicting binning behaviour emerged – personal norms illuminated a significant mediator between social norms, awareness of consequences and binning behaviour. Results of this study endorse the proposed theoretical framework, including the associations among study variables. National park agencies should strengthen the saliency of visitors' personal norms and raise awareness of littering problems and social norms to increase visitors' bin use while visiting the park. Highlights: We studied national park visitors pro-environmental binning behaviour by presenting an Integrated Model of Binning behaviour (IMB) drawing from the theory of planned behaviour and the norm activation model. The model was tested using survey data collected from visitors of Sorkh-e-hesar National Park in Iran. Personal norm is a strong mediator between awareness of consequences and social norms. Awareness of consequences has the highest direct, indirect and specific indirect effect on binning behaviour. This study enhances our understanding of national park visitors' binning behaviour.